Pengaruh Zona Target dan Simulasi Pertandingan dengan Akurasi Pasing Bawah Bola Voli - Bintang Susilo Yudiyono; Dewi Susilawati; Indra Safari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of the target zone method and match simulation on improving the underhand passing accuracy of elementary school students. The method used was an experimental design with a one group pretest–posttest design. The population of this study consisted of fifth-grade students at SDN Malaka, Sumedang Regency, with a sample of 24 students. All participants were given a pre-test to determine their initial ability, followed by treatment using the target zone method and match simulation, and ended with a post-test. The results showed a significant improvement, as evidenced by a significance value (Sig. 2-tailed) of 0.000 (< 0.05). The mean difference value of -4.70833 indicates an improvement in learning outcomes after the treatment. Thus, the target zone method and match simulation were proven to be effective in improving the underhand passing accuracy of elementary school students. Keywords: Volleyball, Underhand Passing, Elementary School, Match Simulation, Target Zone